Kicking Triturus arntzeni when it’s down: large-scale nuclear genetic data confirm that newts from the type locality are genetically admixed - Wielstra, B.; Arntzen, J. W. (Zootaxa, 2014)
We collected nuclear DNA data (52 markers) with next-generation sequencing for nine Triturus newt specimens, including the holotype and two of the paratypes of T. arntzeni, from the type locality at Vrtovać in eastern Serbia. We compare these data to a reference set composed of the four crested newt species distributed in eastern Serbia namely T. cristatus, T. dobrogicus, T. ivanbureschi and T. macedonicus to determine to which of these species the newts from the type locality of T. arntzeni should be attributed. The majority of alleles in individuals from Vrtovać is derived from T. macedonicus, but a considerable number of T. ivanbureschi alleles is also present; alleles typical for T. cristatus and T. dobrogicus are found at low frequency. Accordingly, we interpret Vrtovać as a T. macedonicus – T. ivanbureschi hybrid population, albeit not composed of F1 hybrids but of genetically admixed individuals derived through multiple generations of backcrossing. The data support the notion that the name T. arntzeni should not be applied to a species newly distinguished in T. karelinii sensu lato (to which the name T. ivanbureschi has been given). We conclude that because of the hybrid nature of the individuals from Vrtovać, the name T. arntzeni should be placed not only in the synonymy of T. macedonicus but also in the synonymy of T. ivanbureschi. In this study we demonstrate that next-generation sequencing can provide high quality data for type material with degraded DNA and therefore can play an important role in taxonomy.